Psychopharmacotherapy and comorbidity : conceptual and epistemiological issues, dilemmas and controversies - Jakovljević, Miro (Array, 2009)
Comorbidity is one of the greatest research and clinical challenges to contemporary psychiatry. Mental disorders are often comorbidly expressed, both among themselves and with various sorts of somatic diseases and illnesses. Shifting the paradigm from vertical/mono-morbid interventions to comorbidity and multimorbidity approaches enhances effectiveness and efficiency of human resources utilization. Comorbidity studies have been expected to be an impetus to research on the validity of current diagnostic systems as well as on establishing more effective and efficient treatment including personalized pharmacotherapy